Study of phenolic and mineral components of potato tuber (Solanum tuberosum L) grown in Oued Souf region - Tamma, Noureddine (تامة نور الدين) (Badji Mokhtar-Annaba University, Algeria, 2024)
The chemical detection of the potato's secondary metabolites showed that the extracts contained phenols and flavonoids. The phenolic extract that recorded the highest yield of the potato peel extract of the Al-Trifaoui region was 3.072%. By estimating the total content of phenols using the Folin-Ciocalteu method and estimating the total content of flavonoids using AlCl3 and by UV and visible spectroscopy, it was found that the potato extract from the Ouarmes region contains the largest amount of polyphenols estimated at 72.86 mg EAG/g and also contains the largest amount of flavonoids estimated at 4.095 mg EQ/g, compared to these results with the international standards, which estimated polyphenols between 123-441 mg EAG/100 g. The minerals were quantitatively estimated by volumetric calibration and multiscale visible spectroscopy. The results showed that the highest value was reached for magnesium in the Ouarmes region , which was estimated at 81.15 mg/100 g for the pulp and peels of potato tubers.
Intervention
Keywords: phenolic and mineral components; Solanum tuberosum L